Cubic!

Calculus Level 4

For rational numbers p p and q , q, the area of the shaded region is equal to p + q π . \color{#3D99F6} p+\sqrt{q}\, \pi.

Find 4 p q . 4\sqrt{\frac{\ p\ }{\ q\ }}\, .


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jan 30, 2018

The polar equation of the curve is 1 = r ( cos 3 θ + sin 3 θ ) 1 = r(\cos^3\theta + \sin^3\theta) for 0 θ 1 2 π 0 \le \theta \le \tfrac12\pi . Thus the desired area is A = 1 2 0 1 2 π d θ ( sin 3 θ + cos 3 θ ) 2 = 1 2 0 1 2 π sec 6 θ ( 1 + tan 3 θ ) 2 d θ = 1 2 0 ( 1 + x 2 ) 2 ( 1 + x 3 ) 2 d x = 1 18 0 ( 2 1 + x + 1 + x 1 x + x 2 ) 2 d x = 1 18 0 ( 4 ( 1 + x ) 2 + 4 1 x + x 2 + ( 1 + x ) 2 ( 1 x + x 2 ) 2 ) d x = 1 18 0 ( 4 ( 1 + x ) 2 + 5 1 x + x 2 + 3 x ( 1 x + x 2 ) 2 ) d x = 1 18 [ 4 1 + x + 10 3 tan 1 ( 2 x 1 3 ) 3 2 ( x 2 x + 1 ) ] 0 + 1 12 0 d x ( x 2 x + 1 ) 2 = 11 36 + 10 27 3 π + 1 12 0 d x ( x 2 x + 1 ) 2 \begin{aligned} A & = \; \tfrac12\int_0^{\frac12\pi} \frac{d\theta}{(\sin^3\theta + \cos^3\theta)^2} \; = \; \tfrac12\int_0^{\frac12\pi} \frac{\sec^6\theta}{(1 + \tan^3\theta)^2}\,d\theta \\ & = \; \tfrac12\int_0^\infty \frac{(1 + x^2)^2}{(1 + x^3)^2}\,dx \; = \; \tfrac1{18}\int_0^\infty\left(\frac{2}{1+x} + \frac{1+x}{1 - x + x^2}\right)^2\,dx \\ & = \; \tfrac{1}{18}\int_0^\infty \left(\frac{4}{(1+x)^2} + \frac{4}{1 - x + x^2} + \frac{(1+x)^2}{(1 - x + x^2)^2}\right)\,dx \; = \; \tfrac1{18}\int_0^\infty \left(\frac{4}{(1+ x)^2} + \frac{5}{1 - x + x^2} + \frac{3x}{(1 - x + x^2)^2}\right)\,dx \\ & = \; \tfrac{1}{18}\left[-\frac{4}{1+x} + \frac{10}{\sqrt{3}}\tan^{-1}\big(\tfrac{2x-1}{\sqrt{3}}\big) - \frac{3}{2(x^2-x+1)}\right]_0^\infty + \tfrac{1}{12}\int_0^\infty \frac{dx}{(x^2 - x + 1)^2} \; = \; \tfrac{11}{36} + \tfrac{10}{27\sqrt{3}}\pi + \tfrac{1}{12}\int_0^\infty \frac{dx}{(x^2 - x + 1)^2} \end{aligned} The substitution x = 1 2 ( 1 + 3 tan ϕ ) x = \tfrac12(1 + \sqrt{3}\tan\phi) now gives A = 11 36 + 10 27 3 π + 2 9 3 1 6 π 1 2 π cos 2 ϕ d ϕ = 11 36 + 10 27 3 π + 1 9 3 1 6 π 1 2 π ( cos 2 ϕ + 1 ) d ϕ = 11 36 + 10 27 3 π + 1 9 3 [ 1 2 sin 2 ϕ + ϕ ] 1 6 π 1 2 π = 1 3 + 4 9 3 π \begin{aligned} A & = \; \tfrac{11}{36} + \tfrac{10}{27\sqrt{3}}\pi + \tfrac{2}{9\sqrt{3}}\int_{-\frac16\pi}^{\frac12\pi} \cos^2\phi\,d\phi \; = \; \tfrac{11}{36} + \tfrac{10}{27\sqrt{3}}\pi + \tfrac{1}{9\sqrt{3}}\int_{-\frac16\pi}^{\frac12\pi} (\cos2\phi + 1)\,d\phi \\ & = \; \tfrac{11}{36} + \tfrac{10}{27\sqrt{3}}\pi + \tfrac{1}{9\sqrt{3}}\Big[\tfrac12\sin2\phi + \phi\Big]_{-\frac16\pi}^{\frac12\pi} \; = \; \tfrac13 + \tfrac{4}{9\sqrt{3}}\pi \end{aligned} so that p = 1 3 p = \tfrac13 and q = 16 243 q = \tfrac{16}{243} . Thus 4 p q = 9 4\sqrt{\tfrac{p}{q}} = \boxed{9} .

How did you decide for the substitution x = 1 2 ( 1 + 3 tan ϕ ) x = \tfrac12(1 + 3\tan\phi) ?

Digvijay Singh - 3 years, 4 months ago

Log in to reply

It should be x = 1 2 ( 1 + 3 tan ϕ ) x = \tfrac12(1 + \sqrt{3}\tan\phi) (I have corrected the proof), and it is used because x 2 x + 1 = ( x 1 2 ) 2 + 3 4 x^2 - x + 1 = (x-\tfrac12)^2 + \tfrac34 .

Mark Hennings - 3 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...